**Unformatted text preview: **/3 , we have ourselves a ‘quadratic in disguise’ and we can rewrite x4/3 − x2/3 − 6 = 0
2
as x2/3 − x2/3 − 6 = 0. If we let u = x2/3 , then in terms of u, we get u2 − u − 6 = 0.
Solving for u, we obtain u = −2 or u = 3. Replacing x2/3 back in for u, we get x2/3 = −2
or x2/3 = 3. To avoid the trouble we encountered in the discussion√
following Deﬁnition 5.5,
√
3
3
we √ convert back to radical notation. By interpreting x2/3 as x2 we have x2 = −2
now
3
or x2 = 3. Cubing both sides of these equations results in x2 = −8, which admits no
√
real solution, or x2 = 27, which √
gives x = ±3 3. We construct a sign diagram and ﬁnd
√
x4/3 − x2/3 − 6 > 0 on −∞, −3 3 ∪ 3 3, ∞ . To check our answer graphically, we set
f (x) = x2/3 and g (x) = x4/3 − 6. The solution to x2/3 < x4/3 − 6 corresponds to the
inequality f (x) < g (x), which means we are looking for the x values for which the graph of
f is below the graph of g . Using the ‘Intersect’ command we...

View
Full
Document